Spatial focusing of magnetic particle hyperthermia. Issue 1 (11th December 2019) - Myrovali, Eirini; Maniotis, Nikos; Samaras, Theodoros; Angelakeris, Makis
Abstract : Magnetic particle hyperthermia is a promising cancer therapy, but a typical constraint of its applicability is localizing heat solely to malignant regions sparing healthy surrounding tissues. Abstract : Magnetic particle hyperthermia is a promising cancer therapy, but a typical constraint of its applicability is localizing heat solely to malignant regions sparing healthy surrounding tissues. By simultaneous application of a constant magnetic field together with the hyperthermia inducing alternating magnetic field, heating focus may be confined to smaller regions in a tunable manner. The main objective of this work is to evaluate the focusing parameters, by adequate selection of magnetic nanoparticles and field conditions, and explore spatially focused magnetic particle hyperthermia efficiency in tissue phantom systems comprising agarose gel and magnetic nanoparticles. Our results suggest the possibility of spatially focused heating efficiency of magnetic nanoparticles through the application of a constant magnetic field. Tuning of the constant magnetic field parameters may result in minimizing thermal shock in surrounding regions without affecting the beneficiary thermal outcome in the focusing region.